Uji Toksisitas Subkronik 28 Hari Kombinasi Ekstrak Metanolik Benalu Teh dan Benalu Mangga Terhadap Profil Protein pada Tikus Wistar (Rattus norvegicus) Betina - Umu Intan Kinasih; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
There are 3 indicators for indicating a protein breakdown in the blood through a total protein, albumin, and globulin stability. A compound capable of acting as antioxidants is needed to stabilize the protein's condition. This research is aimed at identifying the toxic effects of extract’s combination from tea parasite and mango parasite on the conditions of blood’s protein by giving EMBTBM constantly for 28 days. The data analysis used ANOVA one-way by SPSS version 17.0. As for the animal test used was a female Wistar rat of 20 with four treatments are control, treatment 1 with a dose of 250mg/Kg body weight (BW). Treatment 2 with a dose of 500mg/Kg body weight (BW) and treatment 3 with a dose of 1000mg/Kg body weight (BW). The result of this research shows that there is no difference between treatment and control over the results of a total protein and albumin. But, at the result of globulin, there is a difference between treatment and control. Therefore, EMBTBM is safe for profile protein and does not cause toxicity because protein is stable and not over-reducing. Keywords:Subchronic,Total Proteins, Albumine, Globuline, Toxicity